Collaborative Governance dalam Penanggulangan Kemiskinan Melalui Program Tasik Bageur di Kota Tasikmalaya - Andi Andi; Astri Siti Fatimah; Mira Oktavia (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
Collaborative governance is a decision-making approach that brings together multiple stakeholders to work toward a shared objective. This study aims to describe the collaborative governance process in poverty alleviation through the Tasik Bageur Program in Tasikmalaya City. Poverty in the city is a multidimensional issue that affects social, economic, and environmental aspects of community life. In response, the Tasikmalaya City Government initiated this program as a collaborative effort involving government institutions, private sector actors, and academic organizations. The program is implemented every Wednesday and is designed to foster cooperation and mutual support in addressing poverty-related needs.Although the program has succeeded in attracting participation from several private and academic actors, this study identifies a major challenge: the number of poor residents remains significantly higher than the number of collaborating partners. This imbalance limits the amount and diversity of assistance provided and reduces the program’s overall effectiveness.This research employs a qualitative descriptive approach, with data collected through observations, interviews, and document analysis. The findings indicate that the collaborative process within the Tasik Bageur Program has not yet reached optimal implementation. Limited understanding and low awareness among private-sector actors hinder broader participation. As a result, the gap between community needs and the available collaborative resources remains substantial.